Răspuns :
a) 3x=×+2
3x-x=2 (se trece numarul dupa egal cu semnul schimbat)
2x=2
x=2:2=1
c) 7x-3=6x
7x-6x=3
x=3
e) 5.8-2+x=5x-1
3.8+x=5x-1
x-5x= -1-3.8
-4x= -4.8
x=1.2
g) 2(x+3)=x+14
2x+6=x+14
2x-x=14-6
x=8
i) 3(x+2)+3=2x+10
3x+6+3=2x+10
3x-2x=10-6-3
x=1
k) 4(x+3)+2(2x-2)=5x+14
4x+12+4x-4=5x+14
4x+4x-5x=14-12+4
3x=6
×=2
m) 7x+5(x+3)-10x=x+20
7x+5x+15-10x=x+20
7x+5x-10x-x=20-15
x=5
o) 4(2x+3)-8=7(x+1)
8x+12-8=7x+7
8x-7x=7-12
x= -5
b) 5x=2x+9
5x-2x=9
3x=9
x=3
d) 5x-4=2x+2
5x-2x=2+4
3x=6
x=2
1) 5x+12=3x+20
5x-3x=20-12
2x=8
x=4
h) x+5+2(x-1)=x+19
x+5+2x-2=x+19
x+2x-x=19-5+2
2x=16
x=8
j) 2(2x+3)+1=3(x+4)
4x+6+1=3x+12
4x-3x=12-6-1
x=5
1) 3(x+2)+2(x+4)=4x+29
3x+6+2x+8=4x+29
3x+2x-4x=29-6-8
x=15
n) 2(x+5)-x+3(x-1)=35
2x+10-x+3x-3=35
2x-x+3x=35-10+3
4x=28
x=7